Rancang Bangun Perpustakaan Buku Digital (E-Book) Berbasis Web - Saputra, Ricco Herdiyan; Waziana, Winia; Baba, Jimi Ali; Magribi, M Ridho; Putra, Aditya Dwi (UIN Raden Intan Lampung, 2021)
One of the efforts to improve the quality of human resources is to foster interest and reading habits. For this reason, the library is expected to become a center for activities that foster interest and reading habits. Libraries have a great responsibility to increase and develop interest and enthusiasm for reading. Information and communication technology (ICT) has become a part of human life today. Therefore, all institutions are competing in the integration of ICT to build and strengthen their knowledge-based talents, to be able to compete in the global era. The need for information technology (IT) is closely related to the role of libraries as a driving force in the preservation and dissemination of scientific information, which develops along with people's activities of writing, printing, educating, and meeting their information needs. The writing of this study uses the descriptive qualitative method and STMIK Pringsewu as the object of the study. The Web-Based Digital Book Library is designed to be easily accessible to readers. Uploaded e-books are created in PDF format. The digital library system can only be accessed locally in the STMIK Pringsewu environment.